Power output prediction for LM wind turbine blade using blade element momentum theory and GH bladed software - Augusto, Gerardo L. (Animo Repository, 2019)
The blade element momentum theory with Prandtl's tip loss and Glauert's correction factors was utilized to compute the power coefficient and to predict the power output of LM rotor blade as a function of hub wind speed ranging from 3 m/s to 25 m/s. The blade length is 43.8 m and consists of five (5) different airfoils. The design tip speed ratio is 8.65 suitable for Class IIA wind turbine which can generate a capacity of 2.5 MW at rated speed of 16 rpm using permanent magnet direct-drive wind turbine generator. The thrust force and driving force profiles in terms of dimensionless blade length as well as the power coefficient and predicted power output were examined and compared with the theoretical equations derived from GH Bladed. Numerical results indicate that there are some degrees of similarities with GH Bladed software output having a maximum power coefficient of 0.49. © Published under licence by IOP Publishing Ltd.